Formation of Si/SiO2 Luminescent Quantum Dots From Mesoporous Silicon by Sodium Tetraborate/Citric Acid Oxidation Treatment - Gongalsky, Maxim B.; Kargina, Julia V.; Cruz, Jose F.; Sánchez-Royo, Juan F.; Chirvony, Vladimir S.; Osminkina, Liubov A.; Sailor, Michael J. (Frontiers in Chemistry, 2019)
We propose a rapid, one-pot method to generate photoluminescent (PL) mesoporous silicon nanoparticles (PSiNPs). Typically, mesoporous silicon (meso-PSi) films, obtained by electrochemical etching of monocrystalline silicon substrates, do not display strong PL because the silicon nanocrystals (nc-Si) in the skeleton are generally too large to display quantum confinement effects. Here we describe an improved approach to form photoluminescent PSiNPs from meso-PSi by partial oxidation in aqueous sodium borate (borax) solutions. The borax solution acts to simultaneously oxidize the nc-Si surface and to partially dissolve the oxide product. This results in reduction of the size of the nc-Si core into the quantum confinement regime, and formation of an insulating silicon dioxide (SiO2) shell. The shell serves to passivate the surface of the silicon nanocrystals, more effectively localizing excitons and increasing PL intensity. We show that the oxidation/dissolution process can be terminated by addition of excess citric acid, which changes the pH of the solution from alkaline to acidic. The process is monitored in situ by measurement of the steady-state PL spectrum from the PSiNPs. The measured PL intensity increases by 1.5 to 2-fold upon addition of citric acid, which we attribute to passivation of non-radiative recombination centers in the oxide shell. The measured PL quantum yield of the final product is up to 20%, the PL activation procedure takes less than 20 minutes, and the resulting material remains stable in aqueous dispersion for at least 1 day. The proposed phenomenological model explaining the process takes into account both pH changes in the solution and the potential increase in solubility of silicic acid due to interaction with sodium cations.